VARIETIES OF BURDEN IN RELIGIOUS ACCOMMODATIONS. Issue 1 (April 2019) - Su, Anna
ABSTRACT: Religious accommodation analysis often takes the form of a tripartite test. One of the factors in such a test is the presence of burden, the current judicial understandings of which have been inadequate to capture a wide range of impact that government regulations have on the individual or community practice of religion. This article considers and compares the jurisprudence of the high courts of the United States and Canada and the European Court of Human Rights and argues for an expansive understanding of the burden requirement in the evaluation of religious accommodation claims, namely to consider burden as (1) coercion, (2) impact, and (3) ratification. I argue that it is imperative to acknowledge different kinds of burden before proceeding to determine its gravity. This approach takes religion more seriously than prevailing approaches and provides for a more equitable distribution of the burden of proof in religious accommodation claims.